Light in the dark : rewriting identity, spirituality, reality - Anzaldúa, Gloria E., 1942-2004; Keating, AnaLouise, 1961- (Durham : Duke University Press, 2015)
"Written during the last decade of her life, Light in the Dark represents the culmination of Gloria E. Anzaldúa's mature thought and the most comprehensive presentation of her philosophy. Throughout, Anzaldúa weaves personal narratives into deeply engaging theoretical readings to comment on numerous contemporary issues-- including the September 11 attacks, neocolonial practices in the art world, and coalition politics ..."--Cover.
boek
Keywords: Creation (Literary, artistic, etc.).; Identity (Psychology).; Mexican American women